Social Development Of Early Childhood Post-Conflict In Kariu Country - Pattiradjwane, Welmin Y; Hetharion, Vinny Alvionita; Ulorlo, Tessya; Ruspanah, Thirsa; Solissa, Selfian Viona (STEBIS Bina Mandiri, 2025)
This study aims to analyze the social development of early childhood post-conflict in Kariu Village, Central Maluku. Early childhood is in a sensitive developmental phase, so traumatic experiences resulting from conflict can impact social skills, emotional regulation, and environmental adaptation. The conflict that occurred in January 2022 forced children to flee and lose a healthy social environment, ultimately leading to psychosocial trauma. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation with 13 children, two early childhood education (PAUD) teachers, and several parents. Data analysis was carried out through the stages of collection, reduction, presentation, and drawing conclusions. The results showed that the conflict had a significant impact on children's social development, particularly in social interaction, emotional regulation, and self-confidence. However, with family support, the role of PAUD teachers, and community involvement, children showed potential for gradual recovery. The conclusion of this study confirms that the social recovery process cannot be achieved instantly but requires long-term interventions based on family, education, and community. The implication of this research is the need for cross-sector collaboration in supporting the social recovery of early childhood post-conflict through trauma healing programs, play-based education, and ongoing psychosocial support